STRATEGI PEMASARAN JASA PENDIDIKAN (ANALISIS PENGEMBANGAN MADRASAH) - Mgs. Nazarudin (Conciencia, 2016)
The existence of Islamic School in the context of national education had not shown to the quality expected in every province there were Islamic schools (State) were built and managed specifically to be a superior Islamic schools. But other Islamic schools that were not built and managed specifically still cannot compete optimally. A form of competition was the quality, integrity, credibility and accountability in the eyes of the community and parents. Islamic schools were still viewed as "an alternative educational institution" which prepared their vacant locals for students who failed to compete at another schools. In connection with it (in order to improve the competitiveness of Islamic schools) might be tried to use marketing models of the industry by market logic approach.